The Distribution, Diversity, and Control of Dirofilariosis in Brazil: A Comprehensive Review - Chocobar, Marianna Laura Elis [UNESP]; Schmidt, Elizabeth Moreira dos Santos [UNESP]; Weir, William; Panarese, Rossella (MDPI, 2024)
Brazil’s extensive coastline, tropical and subtropical climate, and well-preserved environment represent a conducive setting for dirofilariosis, a zoonotic mosquito-borne disease. Although this condition has long been recognised in the country, it has been relatively under-studied, and it is currently considered to be an emerging disease. Diagnosis, treatment, and control remain challenging due to the extensive gaps in knowledge. In order to help address this issue, this review aims to (i) summarise the available literature on the distribution of Dirofilaria spp. in Brazilian dogs over the last decade, (ii) review case reports of dirofilariosis in cats, wild animals, and humans over the last twenty years, and (iii) highlight the benefits of taking a One Health approach to managing this disease. While there have been several prevalence studies in dogs, disease distribution is poorly characterised in cats, and little is known about the occurrence of the parasite in wildlife. Human cases are sporadically reported, and no large-scale studies have been undertaken to date. Evidence indicates that Dirofilaria immitis is the main species circulating in Brazil, although Dirofilaria repens has also been detected. Molecular studies have also suggested the circulation of a highly virulent form of D. immitis, which may be genetically distinct from those of the Old World. A programme of epidemiological, ecological, genomic, and pathogenicity-based studies is required to quantify the impact of dirofilariosis in Brazil on both veterinary and public health and to inform others on its control.
Keywords: diagnosis; Dirofilaria immitis; Dirofilaria repens; genomics; mosquito-borne disease; One Health